2020
DOI: 10.3390/infrastructures5100086
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Dynamic Identification and Monitoring of Bridges in Serviceability Conditions and after Hazardous Events

Abstract: Operational Modal Analysis (OMA) currently represents an appealing technique for the non-destructive assessment and health monitoring of civil structures and infrastructures. Many applications have appeared in the literature in the last decade, demonstrating how this technique can support the observation and understanding of the structural behavior of bridges at different stages of their lifecycle and the remote detection of structural damage. The present paper describes some explanatory applications of OMA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Accordingly, the on-site experimental measure and comparative analysis of vibration parameters for various structural systems and constructional materials are typically associated to efficient early maintenance interventions [15]. Several studies can be found with a focus on variation of vibration frequencies [16,17], modal damping [18,19] or modal shape and curvature [20,21]. In this regard, LG members can be intended as load-bearing components in the same way as traditional constructional systems, and thus susceptible to conventional structural health monitoring procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the on-site experimental measure and comparative analysis of vibration parameters for various structural systems and constructional materials are typically associated to efficient early maintenance interventions [15]. Several studies can be found with a focus on variation of vibration frequencies [16,17], modal damping [18,19] or modal shape and curvature [20,21]. In this regard, LG members can be intended as load-bearing components in the same way as traditional constructional systems, and thus susceptible to conventional structural health monitoring procedures.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noticing that given the 3 main different types of structures (i.e. buildings Dolce et al (2017), bridges and infrastructures Anastasopoulos et al (2021), Giordano et al (2021), Rainieri et al (2020), cultural heritages Kita et al (2019), Potenza et al (2015) and towers Venanzi et al (2020), Gentile et al (2016)) different attentions and instructions must be ensured in the phases of monitoring system design.…”
Section: Introductionmentioning
confidence: 99%
“…Masonry arch bridges are particularly vulnerable to this phenomenon, due to their high stiffness and the usually shallow footings. The relevance of the problem is also witnessed by the increasing number of works dealing with this issue, e.g., numerical studies employing soilfoundation-structure interaction models with different level of complexity [4,9], works proposing advanced models for describing the cracking mechanism evolution in the masonry components [10][11][12][13], and studies oriented towards dynamic identification and scour monitoring [14][15][16][17]. Moreover, besides the studies fully dedicated to the seismic response [18,19], the literature offers an always growing number of papers focused on vulnerability and resilience assessment of masonry bridges under multiple hazard (mainly earthquakes and floods) [20,21].…”
Section: Introductionmentioning
confidence: 99%